PENGARUH KUALITAS PRODUKDAN KESADARAN MEREK TERHADAP KEPUTUSAN PEMBELIAN ULANG MELALUI KEPUASAN KONSUMEN (STUDI PADA KONSUMEN YAMAHA VIXION PT. MATARAM SAKTI SETIABUDI) - Ahmad Falhan Nasith; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2016)
This study is encouraged by the growth of automotive business field particularly the automatic scooter growth which rapidly increasing. This study specifically discusses about the purchase of Yamaha Mio automatic scooter in PT. Yamaha Indonesia Motor Manufacturing Pemuda Semarang that during the year 2011 – 2015 continues to fluctuate on decline of sales and sales target. In case this is not fixed and resolved, it shall cause problems for PT. Yamaha Indonesia Motor Manufacturing Pemuda Semarang in the future. The objective of the study is to perceive the influence of brand image, product quality, and promotion towards the decision of purchasing Yamaha Mio automatic scooter. The type of the study is explanatory, by using questionnaires and interview in collecting data. The sampling method is non-probability sampling that use Purposive Sampling. The sample number is 100 respondents who are end user and purchaser consumers of Yamaha Mio automatic scooter in PT. Yamaha Indonesia Motor Manufacturing Pemuda Semarang. The study uses qualitative and quantitative analysis method. Quantitative analysis using validity, reliability test, correlation coefficient, simple and multiple linear regression analysis, coefficient of determination, significance test (t test and f test), with SPSS as the instrument. The results of the study indicate that brand image (X1), product quality (X2) and promotion (X3) simultaneously affect the consumers purchasing decisions (Y). Based on the results of a two-stage regression, the variable which has the most dominant effect is the promotion (X3). In conclusion, Brand Image, Product Quality and Promotion give positive influence and significance to Purchasing Decisions. Suggestion for Yamaha Mio motorcycle is it had better if doing some innovation by adding technology to its products that meet consumer demands, and for PT. Yamaha Indonesia Motor Manufacturing Pemuda Semarang supposed to provide appealing promotion by giving big amount of discount on its products to increase the purchasing decision.